Production and backreaction of massive fermions during axion inflation with non-Abelian gauge fields. Issue 9 (1st September 2022) - Adshead, Peter; Liu, Aike; Lozanov, Kaloian D.
Abstract: We study the production and backreaction of massive vector-like fermions in the background of a classical SU(2) gauge field during axion-driven inflation. We demonstrate all ultraviolet divergences due to the interactions with the fermions can be absorbed by renormalization of the axion wavefunction and the gauge coupling. The effects of the fermion-axion interaction vanish in the massless limit as required by symmetry. For very massive fermions, contact interactions are induced between the axion, the gauge field and the gravitational field. In this massive limit, we find the usual axion-gauge field interactions are induced, however, in addition we observe the appearance of axion self-interactions, as well as kinetic braiding of the axion with the Einstein tensor. These new axion derivative interactions present intriguing opportunities for model building and phenomenology.